Handling Medical Emergency Conditions During Hajj Flight in a of Syncope Pilgrimage: a Case Report - Asy’ari, Abdurrohman Bagus; Christiadji, Christiadji; Rachmawati, Ermin (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2025)
Background: The role of airplane transportation is very vital in supporting the smooth implementation of the Hajj pilgrimage. Objective: This case report study aims to capture the handling, service, and supervision during the Hajj flight. Results: In the case report of Mrs. M, aged 65 years, an Indonesian Hajj pilgrim from Madiun experienced syncope on the plane during landing. The pilgrim did not receive attention from the medical team or other passengers. Fast-track officers entered the plane that had landed to conduct a screening inspection of the pilgrim's condition. Fast-track officers found a pilgrim in a weak condition who was then subjected to anamnesis and physical examination. The pilgrim was evacuated using a wheelchair, while at the garbarata the fast-track team promptly checked the clinical condition of the pilgrim, vital signs and blood sugar. Vital signs found blood pressure: 160/121 mmHg, saturation: 88% on room air and random blood sugar: 120 mg/dL.  The estimated evacuation process time of fifteen minutes conveyed by the fast-track team to the cabin crew was in accordance with the SOP flow for evacuating sick passengers on the plane. During the evacuation process at the airport at that time there was no doctor on duty and no ambulance driver, so the process of evacuating patients into the ambulance was hampered. Conclusion: Handling of medical emergencies on Hajj flights has not been implemented and understood by officers or Hajj pilgrims and is not yet equipped with sufficient fleet.